A proof of evidence supporting abnormal immunothrombosis in severe COVID-19: naked megakaryocyte nuclei increase in the bone marrow and lungs of critically ill patients. (16th November 2020) - Roncati, Luca; Ligabue, Giulia; Nasillo, Vincenzo; Lusenti, Beatrice; Gennari, William; Fabbiani, Luca; Malagoli, Claudia; Gallo, Graziana; Giovanella, Silvia; Lupi, Massimo; Salviato, Tiziana; Paolini, Ambra; et al.
Abstract: Coronavirus disease 2019 (COVID-19) is a global public health emergency with many clinical facets, and new knowledge about its pathogenetic mechanisms is deemed necessary; among these, there are certainly coagulation disorders. In the history of medicine, autopsies and tissue sampling have played a fundamental role in order to understand the pathogenesis of emerging diseases, including infectious ones; compared to the past, histopathology can be now expanded by innovative techniques and modern technologies. For the first time in worldwide literature, we provide a detailed postmortem and biopsy report on the marked increase, up to 1 order of magnitude, of naked megakaryocyte nuclei in the bone marrow and lungs from serious COVID-19 patients. Most likely related to high interleukin-6 serum levels stimulating megakaryocytopoiesis, this phenomenon concurs to explain well the pulmonary abnormal immunothrombosis in these critically ill patients, all without molecular or electron microscopy signs of megakaryocyte infection.